2004
DOI: 10.1046/j.1529-8817.2004.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral Founder Mutation of the Nude (FOXN1) Gene in Congenital Severe Combined Immunodeficiency Associated with Alopecia in Southern Italy Population

Abstract: SummaryGenetic alterations of the FOXN1 transcription factor, selectively expressed in thymic epithelia and skin, are responsible in both mice and humans for the Nude/SCID phenotype. The first described human FOXN1 mutation was a C792T transition in exon 5 resulting in the nonsense mutation R255X, and was detected in two probands originated from a small community in southern Italy. In this community, four additional children affected with congenital alopecia died in early childhood because of severe infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 11 publications
0
63
0
Order By: Relevance
“…The identification of the full equivalent human phenotype of nude mouse occurred surprisingly about 30 years later with the description of two Italian sisters, who presented congenital alopecia, eyebrows, eyelashes, and nail dystrophy associated with a severe T cell immunodeficiency, as detailed below [2]. The consanguinity of the parents and the small community where the patients originated from suggested an autosomal recessive inheritance [18]. The time gap from the original mouse description led to hypothesize a lethal phenotype in subjects with complete expression.…”
Section: Foxn1 Deficiency In Humans: the Nude Scid Historymentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of the full equivalent human phenotype of nude mouse occurred surprisingly about 30 years later with the description of two Italian sisters, who presented congenital alopecia, eyebrows, eyelashes, and nail dystrophy associated with a severe T cell immunodeficiency, as detailed below [2]. The consanguinity of the parents and the small community where the patients originated from suggested an autosomal recessive inheritance [18]. The time gap from the original mouse description led to hypothesize a lethal phenotype in subjects with complete expression.…”
Section: Foxn1 Deficiency In Humans: the Nude Scid Historymentioning
confidence: 99%
“…In the small community of south Italy, where the first two sisters with FOXN1 deficiency where identified, additional cases of patients with congenital alopecia and early child death because of severe infections were reported [18]. Interestingly, 55 subjects of 843 inhabitants studied were found to carry the heterozygous FOXN1 mutation.…”
Section: Foxn1 Mutations In Heterozygous Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Functional maturation of TEC requires expression of the transcription factor forkhead box n1 (Foxn1); mutations in both mouse Foxn1 and human FOXN1 genes result in athymic and hairless conditions as seen in nude mice and patient with severe combined immunodeficiency syndrome. 5,6 We previously showed that the decline in the expression of Foxn1 in thymic stroma correlates with the onset of reduction in thymocyte numbers and production of naive T cells as determined by the total number of signal joint TCR excised circle (sjTREC) in the thymus, suggesting that Foxn1 may play a role in age-associated thymic involution. 3 Subsequent work by others demonstrated a role of Foxn1 in the cross-talk between TEC and developing thymocytes, which is required for thymopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of the DiGeorge syndrome are a result of the deletion of chromosome 22q11.2, and tbx1 encoded in this region is responsible for the onset of defective thymus development in many DiGeorge syndrome patients [9,10]. It was also shown that mutations in foxn1 in human and mouse can induce the nude phenotype that is characterized by defective thymus development and hairless caused by defective hair follicles (OMIM 601705) [11,12]. Defects in functional thymus development may sometimes result in autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%